The Effects of E-Learning Integration on Students’ attitude of Business Studies Subject in Secondary Schools in Kenya - Kurgat , Susan J. (African Journal of Education,Science and Technology (AJEST), 2015)
The existing trends of academic performance among students in Kenyan schools show that there is need for continued search and adoption of functional innovations in the teaching and learning processes. This paper examined the integrated e-learning approach as one of these new innovations. The study examined the effects of integrated Electronic learning (E-learning) approach on students’ attitudes towards Business Studies subject in secondary schools in Kenya. A descriptive survey research design was adopted. The study was undertaken in the selected E-schools in Kenya. Purposive sampling was used to select the teachers and random sampling technique was used to select the students. A total of three Head teachers, eight Business Studies teachers and 127 Business Studies students participated in the study. Questionnaires and face-to-face interviews were used to collect data from the sample. Both descriptive and inferential statistics were used to analyze the data gathered in the study. Descriptive statistics included use of frequency tables, percentages and mean scores. Inferential statistics involved Analysis of Variance (ANOVA). From the findings, the Integrated E-learning approach has exerted a more positive influence on students’ attitudes towards Business Studies course than the conventional methods. Students demonstrated a more favourable attitude towards learning Business Studies and were highly motivated through integrated E-learning approach than when taught using the conventional approach. The school administration should take a whole-school approach in prioritising development of ICT use in the teaching and learning process. There is the need for a whole school vision and a strategy for ICT. The implementation of ICT is best undertaken in the context of a vision for how it will be used to enhance and extend teaching and learning with an associated commitment and flexible strategy to achieve this. The way the Head teacher demonstrates his/her belief in ICT through action and example is influential.